Deteksi Dini Pertumbuhan dan Perkembangan Anak Usia 0-72 Bulan: Tinjauan Literatur Berbasis Regulasi Kesehatan - Annisaa Nur Faudillah; Lu’lu Rahmadanti; Nur Saadah; Khadijah Khadijah; Homsani Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
Child growth and development are important indicators of the health and well-being of the future generation of a nation. This study comprehensively examines aspects of early detection of growth and development of children aged 0-72 months based on health regulations in Indonesia, specifically PMK RI Number 66 of 2014. The research method uses a library approach with a qualitative descriptive method through analysis of government regulations, scientific journals, and official publications of health agencies. The results of the study indicate that growth is measured through anthropometric indicators including weight, length/height, and head circumference, while development is assessed through five main aspects: physical-motor, social-emotional, communication-language, cognitive, and learning approaches. KPSP is a standard instrument for screening child development in Indonesia at the ages of 3, 6, 9, 12, 15, 18, 21, 24, 30, 36, 42, 48, 54, 60, 66, and 72 months. Various factors influence child growth and development in complex and interrelated ways, including nutritional status, environmental sanitation, parental income and education, immunization history, exclusive breastfeeding, and maternal nutrition during pregnancy. Both undernutrition and overnutrition negatively impact a child's physical, cognitive, and psychosocial development. This study emphasizes the importance of early detection, timely intervention, and a holistic, multifactorial approach to ensuring optimal growth and development of Indonesian children.